Współrządzenie w zarządzaniu obszarami metropolitalnymi - Banachowicz, Beata; Danielewicz, Justyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Globalization processes caused changes in interactions between big cities (metropolis) and areas located near them. This process affects the creation of new relations among different subjects actors in metropolitan area. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 186-198